Enhanced adsorption of aqueous chlorinated aromatic compounds by nitrogen auto-doped biochar produced through pyrolysis of rubber-seed shell. Issue 5 (23rd February 2023) - Wang, Wei; Wang, Zhijuan; Li, Kai; Liu, Yuxin; Xie, Delong; Shan, Shaoyun; He, Liang; Mei, Yi
ABSTRACT: The adsorption of chlorinated aromatic compounds (CACs) on pristine biochar was often limited. Surface modification can greatly improve the adsorption capacity of biochar. In this work, by pyrolysis activation of rubber-seed shell wastes, nitrogen auto-doped biochar (RSS-NBC) was synthesized and used for purifying CACs-containing wastewater. Systematic characterization results showed that after proper treatment, the as-prepared RSS-NBC had high specific surface area, abundant surface oxygen- and nitrogen-containing functional groups, and nano-scale pore structure. Batch adsorption experiments were conducted with using three typical CACs probing pollutants, i.e. 1, 2-dichlorobenzene (1, 2-DCB), 2, 4-dichlorophenol (2, 4-DCP) and 2, 4-dichlorobenzoic acid (2, 4-DCBA). The adsorption experiments results showed that the maximum adsorption amounts of 1, 2-DCB, 2, 4-DCP, and 2, 4-DCBA could reach 2284, 1921, and 1142 mg/g at 298.15 K. Moreover, 90% of the equilibrium adsorption amount can be reached within 0.5 h. The adsorption kinetic results showed that the adsorption processes of the three CACs followed the pseudo-second-order rate model and were dominated by chemisorption. Also, the adsorption isotherms of 1, 2-DCB and 2, 4-DCP belonged to the Freundlich model and were valid for multilayer adsorption, while the adsorption of 2, 4-DCBA followed Langmuir model and single-layer adsorption. The thermodynamics data indicated that the spontaneous adsorption process of 1, 2-DCB and 2, 4-DCP was endothermic while that of 2, 4-DCBA was exothermic. After 5 cycles of adsorption-regeneration, the removal efficiency of RSS-NBC particles still remained more than 80% for the three typical CACs, indicating that it could be reused as an effective and retrievable adsorbent in the treatment of CACs-containing effluents. GRAPHICAL ABSTRACT: UF0001